2008
DOI: 10.1111/j.1468-0297.2008.02138.x
|View full text |Cite
|
Sign up to set email alerts
|

Publicity of Debate and the Incentive to Dissent: Evidence from the US Federal Reserve

Abstract: When central banks are transparent about their decision making, there may be clear benefits in terms of credibility, policy effectiveness, and improved democratic accountability. While recent literature has focused on all of these advantages of transparency, in this paper we consider one potential cost: the possibility that publishing detailed records of deliberations will make members of a monetary policy committee more reluctant to offer dissenting opinions. Drawing on the recent literature on expert advisor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(122 citation statements)
references
References 34 publications
1
108
2
Order By: Relevance
“…1 Chappell et al (1993) find that partisan behavior is partially attributable to the career backgrounds of FOMC members, noting that "experience in government, particularly at the Federal Reserve Board, is associated with significantly stronger preferences for monetary ease" (p.130). Adolph (2005) uncovers similar findings, and more recently, Meade and Stasavage (2008) have introduced a role for career concerns, suggesting that members of a monetary policy committee are less likely to voice dissent when the transcripts of FOMC meetings are placed in the public domain. 2 As a primary motivation of this paper is to test the model of Havrilesky and Schweitzer (1990), it is to their contribution which attention now briefly turns.…”
Section: Relationship To the Literaturementioning
confidence: 64%
“…1 Chappell et al (1993) find that partisan behavior is partially attributable to the career backgrounds of FOMC members, noting that "experience in government, particularly at the Federal Reserve Board, is associated with significantly stronger preferences for monetary ease" (p.130). Adolph (2005) uncovers similar findings, and more recently, Meade and Stasavage (2008) have introduced a role for career concerns, suggesting that members of a monetary policy committee are less likely to voice dissent when the transcripts of FOMC meetings are placed in the public domain. 2 As a primary motivation of this paper is to test the model of Havrilesky and Schweitzer (1990), it is to their contribution which attention now briefly turns.…”
Section: Relationship To the Literaturementioning
confidence: 64%
“…Indeed, recent theoretical literature has shown that reputational concerns influence committee behaviour differently under secrecy and transparency in the case of political committees (e.g. Stasavage (2007)), corporate boards (Malenko (2013)), and monetary policy committees (Levy (2007); Visser and Swank (2007); Swank and Visser (2013); Swank et al (2008); Meade and Stasavage (2008); Gersbach and Hahn (2008)). …”
Section: Introductionmentioning
confidence: 99%
“…Here, the argument has been made that too much transparency could be harmful (Meade and Stasavage (2008); Swank et al (2008); Swank and Visser (2013)). This debate over transparency is not a recent phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…While theoretical research has mainly focused on the welfare effects of increased transparency (Morris and Shin, 2002, Angeletos and Pavan, 2007, Cornand and Heinemann, 2008, Dale et al, 2011, Hahn, 2012, empirical research has examined the implications of increased transparency with respect to monetary policy predictability (Gerlach-Kristen, 2004, Crowe, 2010, Sturm and de Haan, 2011, Horvath et al, 2012a, macroeconomic outcomes (Dincer and Eichengreen, 2014) and dissent among central bankers (Meade and Stasavage, 2008).…”
Section: Introductionmentioning
confidence: 99%